Does relative deprivation induce migration?: evidence from Sub-Saharan Africa - Kafle, Kashi; Benfica, Rui; Winters, P. (Wiley, 2020)
This analysis revisits the decades-old relative deprivation theory of migration. In contrast to the traditional view that migration is driven by absolute income maximization, we test whether relative deprivation induces migration in the context of sub-Saharan Africa. Taking advantage of the internationally comparable longitudinal data from integrated household and agriculture surveys from Tanzania, Ethiopia, Malawi, Nigeria, and Uganda, we use panel fixed effects to estimate the effects of relative deprivation on migration decisions. Using per capita consumption expenditure and multidimensional wealth index as well-being measures, we find that a household’s migration decision is based not only on its absolute well-being level but also on the relative position of the household in the well-being distribution of the community in which it resides. We also discover that the effect of relative deprivation on migration is amplified in rural, agricultural, and male-headed households. Results are robust to alternative specifications including the use of Hausman Taylor Instrumental Variable (HTIV) estimator and pooled data across the five countries. Results confirm that the “migration-relative deprivation” relationship also holds in the context of sub-Saharan Africa. We argue that policies designed to check rural–urban migration through rural transformation and poverty reduction programs should use caution because such programs can increase economic inequality, which further increases migration flow.